A prospective randomized study to compare tramadol and morphine for postoperative analgesia in spine surgeries using intravenous patient controlled analgesia - Javed, Tasaduq; Ahad, Basharat; Singh, Pushpinder; Ahmad, Riyaz (International Journal of Research in Medical Sciences, 2017)
Background: Spine surgeries particulary spine fusion surgeries provide a unique challenge with respect to postoperative analgesia as the choices to provide analgesia are limited. Uses of NSAIDS and neuroaxial anaesthesia for post-operative analgesia in spine surgeries have been controversial. Patient controlled analgesia with opioids is commonly used and morphine remains the gold standard. The aim of this study was to compare tramadol with morphine for postoperative analgesia in spine surgeries using iv patient controlled analgesia. Methods: A total of 80 adult patients of ASA grade I and 2 undergoing spine surgeries and divided into two groups i.e. morphine group M and tramadol group T with 40 patients in each group were included in the study. pain assessment was done by NRS (numeric rating scale) upto 48 hours postoperatively other parameters like nausea/vomiting and sedation were also noted. Both groups received boluses initially to control pain. Group M patients received 1mg i.v demand dose of morphine with lock out time of 10-15 minutes and in Group T patients PCA device was set to deliver 20mg i.v demand dose of tramadol with lock out time of 10-15 minutes. A bolus of 25mcg fentanyl was given as rescue analgesia in both groups by the nurse if required. No background infusion or four-hour maximal limit was set on PCA pumps. Results: Pain scores remained on lower side in both the groups, though slightly better with morphine and the difference was statistically significant at 4 hours, 12 hours and 24 hours. The total NRS mean value (0-48 hours) of morphine and tramadol is 3.270 and 3.629 with p value of 0.015 which is statistically significant. 7 patients in morphine group received rescue analgesia while it was received by 15 patients in tramadol group with p value of 0.78 which is statistically insignificant. Nausea and Vomiting was encountered more frequently in the tramadol group. Mean mobilization time in patients of tramadol group was 21.72 hours and that of morphine group was 17.10 hours with p value of 0.00 which is highly significant. Conclusions: Morphine and tramadol when used in PCA mode provide adequate pain relief post operatively after spine surgeries with morphine showing slightly better analgesia profile and significantly less nausea and vomiting than tramadol.